N(6)-methyladenosine is required for the hypoxic stabilization of specific mRNAs - Fry, Nate J. (RNA, 2017)
Post-transcriptional regulation of mRNA during oxygen deprivation, or hypoxia, can affect the survivability of cells. Hypoxia has been shown to increase stability of a subset of ischemia-related mRNAs, including VEGF. RNA binding proteins and miRNAs have been identified as important for post-transcriptional regulation of individual mRNAs, but corresponding mechanisms that regulate global stability are not well understood. Recently, mRNA modification by N(6)-methyladenosine (m(6)A) has been shown to be involved in post-transcriptional regulation processes including mRNA stability and promotion of translation, but the role of m(6)A in the hypoxia response is unknown. In this study, we investigate the effect of hypoxia on RNA modifications including m(6)A. Our results show hypoxia increases m(6)A content of poly(A)(+) messenger RNA (mRNA), but not in total or ribosomal RNA in HEK293T cells. Using m(6)A mRNA immunoprecipitation, we identify specific hypoxia-modified mRNAs, including glucose transporter 1 (Glut1) and c-Myc, which show increased m(6)A levels under hypoxic conditions. Many of these mRNAs also exhibit increased stability, which was blocked by knockdown of m(6)A-specific methyltransferases METTL3/14. However, the increase in mRNA stability did not correlate with a change in translational efficiency or the steady-state amount of their proteins. Knockdown of METTL3/14 did reveal that m(6)A is involved in recovery of translational efficiency after hypoxic stress. Therefore, our results suggest that an increase in m(6)A mRNA during hypoxic exposure leads to post-transcriptional stabilization of specific mRNAs and contributes to the recovery of translational efficiency after hypoxic stress.